TWO DIMENSIONAL HORIZONTAL MODEL OF DISTRIBUTION TEMPERATURE IN COASTAL WATERS AROUND OUTLETS OF PLTGU MUARA TAWAR, BEKASI REGENCY BY USING CELLULAR AUTOMATA - (NIM: 22410305); pembimbing: Dr. rer. nat. Dadang K. Mihardja, APRIANSYAH
In this study, cellular automata model (MCA) has been applied in the waters around outlet of PLTGU Muara Tawar, Bekasi regency to modeled of the spreading of temperature by the advection, diffusion and interaction of sea air. The simulation was performed using the velocity field at the moment to ebb and tide. Velocity field obtained from the numerical model interpolation (Mihardja, et al, 2011). In the cellular automata model is done in synthetic and field area. The simulation results in the synthetic area indicated that the verification of cellular automata model (MCA) with the Analytical Model (MA) and Numerical Model (MN) produced good temperature distribution patterns. Error percentage of MCA to MA is 3.79% (scenario 1) and 6.89% (scenario 2), while the percentage error of MCA to MN is 7.90% (scenario 1) and 4.64% (scenario 2). The simulation results in the waters around the outlet of PLTGU Muara Tawar showed that patterns of temperature distribution at the moment to ebb and tide is suitable among MCA, field measurement data and MN. Validation results of MCA to field measurement data and MN (Mihardja, et al, 2011) produced small error in the range 2 Ã‚Â–8%.